Absence of link between abortion and seropositivity of cystic hydatid disease in ewes and female goats in Turkey - Simsek, Sami; Risvanli, Ali; Zonturlu, Abuzer Gaffar; Demiral, Orkun; Saat, Nevzat (Ist Zooprofilattico Sperimentale Abruzzo & Molise G Caporale-Izs A&M, 2012)
This study was conducted to test whether there is a statistically significant association between seropositivity to cystic echinococcosis and abortion in ewes and female goats from the Turkish provinces of Elazig (east Anatolia), Sanliurfa (south-east Anatolia) and Kayseri (Inner Anatolia) using the enzyme-linked immunosorbent assay (ELISA). A total of 20 of 133 sera (15.1%) from ewes and 5 of 101 sera (4.9%) from goats with a history of abortion gave seropositive results that were not significantly different (p>0.05) from these, 9.9% (10/101) were reported for ewes and 1.6% (2/122) for female goats without a history of abortion. Serological prevalence rates among those animals with a history of abortion were not significantly different from the control group. No positive association was established between seropositivity for cystic echinococcosis and abortion in ewes and female goats.
Keywords: Abortion; Anatolia; ELISA; Enzyme-linked immunosorbent assay; Ewe; Hydatid disease; Goat; Turkey